On elementary domains of partial projective representations of groups - Pinedo, H. (Algebra and Discrete Mathematics, 2013)
We characterize the finite groups containing only elementary domains of factor sets of partial projective representations. A condition for a finite subset A of a group G, which contains the unity of the group, to induce an elementary partial representation, of G whose (idempotent) factor set is total is given. Finally, we characterize the elementary partial representation of abelian groups of degrees ≤ 4 with total factor set.